Layanan Bimbingan Kelompok dengan Teknik Self-Regulation Untuk Meningkatkan Motivasi Belajar Mahasiswa - Hadi Pranoto; Nurul Atieka; Retno Fajarwati; Rio Septora (Universitas Mathla'ul Anwar Banten, 2018)
GROUP GUIDANCE SERVICES WITH SELF-REGULATION TECHNIQUE TO IMPROVE STUDENT LEARNING MOTIVATION. Learning Learning Motivation students before being given group guidance with self-regulation techniques, knowing Learning Motivation students after given group guidance with self-regulation techniques, knowing the effectiveness of group guidance with self-regulation technique to improve Learning Motivation Student Study Program Guidance and the Counseling Muhammadiyah University of Metro. The long-term goal target after this research is to design a program or model of group guidance with self-regulation techniques in improving learning motivation for Higher Education Level. Sampling in this study using Probability Sampling technique in the form of Simple Random Sampling, which is taking the sample members of the population done randomly without regard to the strata in the population. The subject of the study is the University Muhammadiyah of Metro Student Guidance Study and Counseling Study Program without considering certain criteria. The measuring tool used is the scale of Learning Motivation (learning motivation). The experimental method of one group pretest-posttest design. The results of Group Guidance services with self-regulation techniques can improve the learning motivation of University Muhammadiyah of Metro Guidance and Counseling Study Program students.